Long-term population trends of the Red-legged Cormorant Phalacrocorax gaimardi on the Argentine coast - Millones, Ana (2015)
The world population of Red-legged Cormorant Phalacrocorax gaimardi is reasonably small and has showed rapid declines. In Argentina, this species breeds in 13 localities and is considered as 'Endangered' by the national government. In this study, we provide information about population trends of the Red-legged Cormorant on the Argentine coast, between 1990 and 2009. We also discuss whether these trends could be related to sea surface temperature and marine primary productivity, both of which are considered oceanographic factors that can affect breeding seabirds. The long-term trend in the breeding population showed a slight decrease of 1.2% per year. Seven colonies showed an average population change < 1. Periods of stability and increase were identified over the study period, but they were insufficient to compensate for the decreases. The largest colony of Red-legged Cormorants (La Mina, with more than 55% of the entire breeding population) seems to determine the overall population trend. We did not find a direct relationship between the overall number of Red-legged Cormorants and the two oceanographic factors analysed. However, our analysis detected a positive effect of ocean productivity close to the coast on the largest colony at the beginning of the breeding season, suggesting that coastal ocean productivity could be an important factor affecting temporal variations in the Argentinian population.